Prophylaxis of Macular Edema with Intravitreal Ranibizumab in Patients with Diabetic Retinopathy after Cataract Surgery: A Pilot Study. (16th June 2011) - Udaondo, Patricia; Garcia-Pous, Maria; Garcia-Delpech, Salvador; Salom, David; Diaz-Llopis, Manuel
Abstract : The purpose of this study was to evaluate the effectiveness of intravitreal ranibizumab (Lucentis, Genentech, South San Francisco, Calif, USA) combined with cataract surgery for the prevention of clinically significant macular edema (CSME) in patients with diabetic retinopathy (DR). This prospective interventional case series included fifty-four eyes of 54 patients with a previous diagnosis of nonproliferative diabetic retinopathy (NPDR) without macular edema preoperatively. Subjects were assigned in a 1 : 1 ratio to receive an intraoperative intravitreal ranibizumab injection (n = 27 ) or not (control group, n = 27 ) associated with standardised phacoemulsification surgery. The main outcome measure was the incidence of CSME one and three months after surgery. One month after surgery the incidence of CSME in the control group was 25.92% and 3.70% in the treatment group and at three months was 22.22% and 3.70%, respectively. Short-term results suggest that intravitreal ranibizumab immediately after phacoemulsification prevents CS ME in patients with NPDR.